Panel summary: Preventing and managing infectious diseases among people who inject drugs in Ontario - Waddell, K; Wilson, MG (My University, 2019)
A thematic summary of what was learned from the citizen panel on preventing and managing infectious diseases among people who inject drugs in Ontario, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: infectious diseases; drugs; Ontario